Reactive molecular dynamics simulation in the early stage of naphthalene carbonisation. Issue 15 (13th October 2021) - Yang, Haiyang; Wang, Lixin; Zhou, Han; Song, Hao; Wang, Chunlu; Ren, Qiang; Fan, Qiming
ABSTRACT: Molecular simulation methods were utilised to do research into reactive molecular dynamics in the early stage of naphthalene carbonisation. The structural properties and charge distribution of naphthalene were investigated by the quantum chemistry. The net charge distributed on α -position carbon atom was slightly more than that on β -position carbon atom, and the reaction activity of α -position carbon atom was stronger. Reactive force field ReaxFF was used to simulate reactive molecular dynamics. Condensation, pyrolysis, rearrangement and hydrogen transfer reactions happened during the simulation. And the main reaction route in the early stage of naphthalene coking process was acquired. The formation of free radical was initiated by the intermolecular hydrogen transfer reaction rather than homolytic C−H bond dissociation. The reaction mechanism may provide theoretical guidance for the practical production of needle coke.